2006
DOI: 10.1007/s11136-006-0026-8
|View full text |Cite
|
Sign up to set email alerts
|

The ORTHO BC-SAT – a satisfaction questionnaire for women using hormonal contraceptives

Abstract: Our results support the reliability and validity of the ORTHO BC-SAT. It may be used in future studies to evaluate satisfaction among hormonal contraceptive users.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 11 publications
0
21
0
Order By: Relevance
“…Clinical practitioners and young women may find that in addition to tolerability, efficacy, and acceptability (52)(53)(54) there are important vascular benefits from using the vaginal ring compared with other hormonal contraceptive options. …”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Clinical practitioners and young women may find that in addition to tolerability, efficacy, and acceptability (52)(53)(54) there are important vascular benefits from using the vaginal ring compared with other hormonal contraceptive options. …”
Section: Limitations and Future Perspectivesmentioning
confidence: 99%
“…Despite limited application of the framework to prevention, findings from the qualitative studies described earlier are consistent with the framework’s adherence constructs. Predisposing factors which emerged in the qualitative HIV prevention literature and for which we identified potential screening measures include: reasons for trial participation [ 29 36 ]; beliefs about clinical trials or the products being tested [ 37 , 38 ]; and personal attributes such as commitment, self-efficacy, or agency [ 21 , 38 – 40 ]. The literature review also identified barriers and facilitators of adherence that might be experienced once a trial participant began using the study product and which could be assessed over time, including: the beneficial or negative impact of trial staff [ 38 , 41 , 42 ]; practical constraints, including travel, cost of participation, and impact on daily life [ 22 , 37 , 43 , 44 ]; experience of side effects [ 44 46 ]; and impact of stigma [ 30 , 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical practitioners and young women may find that in addition to tolerability, efficacy, and acceptability (5254) there are important vascular benefits from using the vaginal ring compared with other hormonal contraceptive options.…”
Section: Discussionmentioning
confidence: 99%